Probing Bacterial Interactions with the Schistosoma mansoni-Killing Toxin Biomphalysin via Atomic Force Microscopy and Single Molecule Force Spectroscopy - Jihen Zouaoui; Pierre Poteaux; Audrey Beaussart; Nicolas Lesniewska; David Duval; Jérôme F. L. Duval (Toxins)
Recent work has identified biomphalysin (BM) protein from the snail Biomphalaria glabrata as a cytolytic toxin against the Schistosoma mansoni parasite. Ex vivo interactome studies further evidenced BM’s ability to bind bacterial outer membrane proteins, but its specific antibacterial mechanisms and selectivity remain unclear. Accordingly, this study aims to elucidate the interaction between BM and two model bacteria with distinct cell surface architectures: Escherichia coli (Gram−) and Micrococcus luteus (Gram+). Employing a multiscale approach, we used in vivo single-molecule force spectroscopy (SMFS) to probe molecular interactions at the single cell level. Combined with cell aggregation assays, immunoblotting and Atomic Force Microscopy (AFM) imaging, SMFS results evidenced a selective interaction of BM from snail plasma with M. luteus but not E. coli. Exposure of M. luteus to BM compromised cell surface integrity and induced cell aggregation. These effects correlated with a patch-like distribution of BM on M. luteus reminiscent of pore-forming toxins, as revealed by the anti-BM antibody-functionalized AFM tip. Overall, this work highlights the utility of SMFS in dissecting host–pathogen molecular dialogs. It reveals BM’s selective action against M. luteus, potentially via surface clustering, and it shows spatially heterogeneous responses to the toxin within and between individual cells.